APPLICATION OF GENERATORS OF PSEUDO-RANDOM NUMBERS AND SEQUENCES IN CYBER SECURITY, METHODS OF THEIR CONSTRUCTION AND QUALITY ASSESSMENT - Khomik, Mariia; Harasymchuk, Oleh (Ukrainian Information Security Research Journal, 2023)
Due to the rapid development of computing and measurement technology, as well as the implementation of advanced technologies, the scope of application for pseudo-random number generators and pseudo-random sequences has significantly expanded, placing new demands on their design and quality evaluation methods. Quality pseudo-random sequences, although essentially deterministic, possess nearly all the properties of true random processes and successfully replace them, as the generation of random sequences is extremely complex. Due to the diversity and wide range of tasks that require the use of pseudo-random numerical sequences, new algorithms, methods, and tools for obtaining such sequences are constantly being developed and improved. Using pseudo-random sequence generators, one can obtain sequences of numbers where each element is practically independent of others and follows a specific prescribed distribution law, with the uniform distribution being the most common. Thanks to their statistical properties and generation speed, pseudo-random number and sequence generators are essential tools in various fields, including simulation modeling (economic, mathematical, physical, medical research, military applications), computer game development (generation of 3D models, textures, and worlds, as well as creating diversity and randomness in the behavior of characters and events), and measurement technology. Overall, it's important to note that developers of pseudo-random sequence generators face a set of stringent requirements regarding specific characteristics of the results they create using these generators. These requirements can vary depending on the generator's intended purpose and can be particularly high and demanding when pseudo-random sequences are used in cybersecurity and information protection. For example, for cryptographic applications, the requirements are extremely rigorous and may sometimes even contradict each other. To verify whether the generated sequence meets the specified criteria and requirements, it is necessary to evaluate its quality, which involves assessing various features and parameters. Since the development of pseudo-random sequence generators aims to make them resemble sequences of truly random numbers, the basis for any evaluation of generators lies in comparing the statistical characteristics of the generated sequence with the characteristics of truly random sequences. For this purpose, various tests are used, which allow the detection of existing statistical regularities and, thus, the identification of low-quality pseudo-random sequences.